1187. Analysis of the Clonal Recovery Pattern of Enterococcus faecium to Evaluate the Efficacy of Pulsed Xenon Ultraviolet Light (PX-UV) in Bioburden Reduction. (15th December 2022) - Ashby, Landon; Navarathna, Thanuri; Chatterjee, Piyali; Hwang, Munok; Choi, Hosoon; Dhar, Sorabh; Kaye, Keith S; Jinadatha, Chetan
Abstract: Background: Enterococcus faecium (E. faecium) is a common hospital-associated infection (HAI) that can lead to increased costs, morbidity, and mortality. Pulsed Xenon Ultraviolet light (PX-UV) has been shown to reduce bacterial bioburden levels on surfaces. This study aims to assess the effect of the addition of PX-UV to terminal cleaning on the clonal recovery of E. faecium sequence types (STs) using Whole Genome Sequencing (WGS) on patient isolates. Methods: During 2017 to 2020 a prospective, randomized, double-blinded, sham-controlled, interventional, crossover trial in 2 separate Detroit hospitals (H1 and H2) compared HAI counts after the addition of either PX-UV or a non-UV sham device to terminal cleaning methods. The trial consisted of a total of 16 units randomized to have either the treatment of PX-UV (Group Q) or the sham control device with no UV (Group W) for 12 months. A washout period (Group R) of 6 months followed and the trial concluded with a 12-month crossover of treatments. A total of 60 E. faecium samples were collected, then WGS was performed by the Illumina Nextseq 550 instrument. de novo assembly was preformed using the SPAdes program. Whole Genome Multilocus Sequence Type (wgMLST) analysis was performed by BioNumerics (v7.6) to construct minimum spanning tree (MST). Results: A total of 7 STs were obtained across the 2 hospitals (H1 and H2). ST117, ST17, and ST80 all had more than 10 total recovered isolates, ST117 being the most frequent with 24 isolates. Less than 3 isolates were recovered for all other STs. For all STs, Group Q (PX-UV) had 14, Group R (washout period) had 22, and Group W (non-UV sham) had 24. ST18 was only found in Group Q. ST412, ST584, and ST736 were not found in Group W. The data shows that the intervention PX-UV group had a reduction of clonal recovery by 10 STs as compared to the sham UV group. Table 1: Total number of each sequence type (ST) in H1 and H2 Conclusion: The overall reductions in the number of isolates in the real UV units was driven by reductions in the ST117 a predominant strain in a hospital environment reported previously in Detroit and ST80. There were negligible differences in recovery of other ST between the groups. The reduction in clonal recovery of E. faecium isolates in Group Q as compared to Group R might be related to use of PX-UV following terminal room cleaning. Disclosures: Piyali Chatterjee, PhD, AHRQ Grant # 1R03HS027667-01: Grant/Research Support|AHRQ Grant # 1R03HS027667-01: Central Texas Veterans Health Care System Keith S. Kaye, MD, MPH, Allecra: Advisor/Consultant|GlaxoSmithKline plc.: Receiving symposia honoraria|GlaxoSmithKline plc.: GlaxoSmithKline plc.-sponsored study 212502|Merck: Advisor/Consultant|qpex: Advisor/Consultant|Shionogi: Grant/Research Support|Spero: Advisor/Consultant Chetan Jinadatha, MD, MPH, AHRQ R01 Grant-5R01HS025598: Grant/Research Support|EOS Surfaces: Copper Coupons and materials for testing.